The Effect of Hypnotherapy to Reduce Dysmenorrhea Pain - Sherly Amelia; Ratna Dewi; Wiwit Febrina (Universitas Padjadjaran, 2020)
The Incidence of primary dysmenorrhea in Indonesia is around 54.89%, the remaining 45.11% is secondary dysmenorrhoea. Dysmenorrhoea in Parabek high school students out of 35 students, 25 students experience dysminor when menstruation. One of the non-pharmacological dysmenorrhoea treatments is hypnotherapy. Hypnotherapy is an easy, fast, effective, and efficient way to reach the subconscious mind. This study aims to determine the effect of hypnotherapy on dysmenorrhoea in high school students. The research method used was pre-experimental with are search design one group pre-test post-test. The total population obtained was 117 people and the number of samples taken was 20 people, with a purposive sampling technique. Data collection was obtained directly from respondents using the measuring instrument Verbal Descriptor Scale (VDS). Data analysis was carried out in two stages, namely univariate and bivariate using the dependent t-test. The results showed that the average value of the dysmenorrhoea scale before the intervention was given was 6.50 and the average value after intervention was 1.35, there was an effect of hypnotherapy on dysmenorrhoea (t = 17.596, p-value= 0.001). Hypnotherapy can be suggested to be applied as a non-pharmacological measure to treat dysmenorrhea. .